Relativisme dalam Isu Pernikahan Sesama Jenis: Analisis Epistemologi Tauhid Naquib Al-Attas - Aqilah Bakhtiar, Inayah; Naya, Arsya; Ave Hidayatullah, Elit; Mujahidah, Basmah (Zawiyah: Jurnal Pemikiran Islam, 2025)
This article examines the rise of epistemological relativism that emerges from the loss of authority and trust in the notion of absolute truth. The phenomenon of same-sex marriage has become a controversial issue in society, influenced by Michel Foucault’s concept of truth and power, which views truth as a subjective construct shaped by power relations. Same-sex marriage operates within legal and political systems that are not universally accepted across all countries, cultures, or religions. Dewesternization arises as an effort to restore the Islamic worldview as the primary framework for understanding knowledge, reality, and life. The research method employed is library research using an epistemological and philosophical approach, accompanied by a comparative analysis between the thoughts of Michel Foucault and Muhammad Naquib al-Attas. The main reference used in this study is Muhammad Naquib al-Attas’s book Islam and Secularism. The purpose of this study is to analyze the root problems of epistemological relativism that influence human perceptions of truth and to propose an alternative solution through the revitalization of M. Naquib al-Attas’s tawhidi epistemology as a foundation for strengthening absolute and divine truth. The findings reveal that the revitalization of tawhidi epistemology can restore the unity between intellect and soul within the framework of divine oneness. Therefore, this study emphasizes the urgency of reconstructing the Islamic knowledge paradigm to counter cultural relativism and the ongoing moral crisis in the post-truth era.